chlamydia pneumoniae unfection in - patients with community acquired pneumonia in Iraq - Salman, hayfaa D. (Journal of the Faculty of Medicine Baghdad, 2009)
Backgrund: This study was carried out to determine the prevalence of chlamydia the pneumonia in community-acquired pnevmonia in Iraq.